PENGELOLAAN KEARSIPAN PERKARA DI PENGADILAN DALAM RANGKA KEMUDAHAN AKSES INFORMASI PUBLIK DI PENGADILAN TATA USAHA NEGARA MAKASSAR - Muhammad Rizaldi Rahman (Jurnal Hukum Peratun, 2020)
Since the birth of the reform era in Indonesia the administration of government refers to the principles of Good Governance and General Principles of Good Governance. In order to accommodate the realization of good governance, a Law on Public Information Disclosure was established which mandates that every Public Agency must develop a system of information and documentation to manage Public Information properly and efficiently so that it can be easily accessed. No exception with the Mahkamah Agung which is committed to providing the best service to the public by realizing openness of information in the Court. Administrative Court of Makassar as a judicial body is also inseparable from the obligation to realize information disclosure in the Court. The purpose of this paper is to find out the implementation of the information disclosure service regarding archives at the Administrative Court of Makassar. Data collection is done through field observations and interviews with several related parties.